Village Owned Enterprise (BUMKal) Development Strategy: Case Study on BUMKal Bangkit Karya Bangunharjo Village Sewon Subdistrict Bantul Regency - Anggra Widyaningrum; Agnes Ratih Ari (International Journal of Technology and Education Research, 2025)
Village-Owned Enterprises (BUMKAL) were born as a new approach in efforts to improve the village economy based on village needs and potential. The purpose of this research is to find out the description, internal and external factors, as well as find out alternative strategies that can be implemented in the development of BUMKAL Bangkit Karya. The research method in this study uses descriptive qualitative methods with SWOT analysis techniques. This research was conducted for approximately two months, with stages of observation, interviews, documentation and data analysis. Based on the results of the SWOT analysis that has been carried out, it can be seen that the position of Bumkal Bangkit Karya Bangunharjo is in Quadrants 1.13 and 0.47. This shows that Bumkal Bangkit Karya Bangunharjo is included in quadrant I, namely Aggressive Strategy, is in a strong position with strengths and opportunities that are far greater than weaknesses and threats. Aggressive strategies that are more prominent and have a big influence on the development of Bumkal Bangkit Karya Bangunharjo are as follows: (1) Utilizing village potential by forming new business fields, (2) Optimizing the performance of Bumkal Bangkit Karya with technological developments, (3) Collaborating with other parties (investors) in holding activities that can optimize sub- district assets, (4) Increasing activities that involve the community in them so that Bumkal is felt to be present by the community.